Gengobot: Chatbot application to enhance N4 Level Students’ Japanese grammar ability - Rifai, Mumu Muhammad; Haristiani, Nuria; Risda, Dianni (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2020)
This study aims to compare students’ Japanese language grammar ability, between students who practice with a chatbot-based application (Gengobot) with students who do not use the application. This research was conducted using quantitative experimental research methods, with experimental class and control class. The subjects of this research were 22 Japanese language students. The results showed that the grammar ability of students who used Gengobot application as a training medium improved significantly than students who used conventional media as paper works. Factors that cause these differences are the use of cognitive and behavioristic approaches in applications, as well as the use of media, which is more practical and engaging. The questionnaire regarding student responses to the Gengobot application shows positive results. Things that need to be considered in future research are the development of the Gengobot application to be more flexible and to add more material to the application.